Behebung eines Webfehlers: Wie die Konjunkturkomponente demokratisch legitimiert und nachhaltiger werden könnte; Fixing a design error - Florian Schuster; Philippa Sigl-Glöckner (Wirtschaftsdienst, 2022)
– The optimisation of the cyclical adjustment procedure under the German debt brake should focus on how to contribute to a democratically legitimate and sustainable fiscal policy. In this article, we discuss four criteria that should be satisfied: The method must (i) be sufficiently determined, (ii) take the current state of research into account, (iii) incentivise a policy that enhances supply-side capacities, and (iv) be transparent. We show that today's form of the cyclically adjusted budget balance does not satisfy these criteria, and we propose a reform. Finally, we discuss several recent trends in German fiscal policy, questioning whether such a reform can save the debt brake's plausibility.
Keywords: E24; E62; H63; 330